Warsaw aerostatic spectacles in the 18th and 19th centuries. Selected episodes - Kurek, Krzysztof (Relacyjność w kulturze i sztuce: Księga jubileuszowa Profesor Małgorzaty Leyko, 2025)
The author presents the history of balloon flights organised in Warsaw in the 18th and 19th centuries. He refers in his reflections to both the history of technology and the history of performance. The aerostat flight spectacles became one of the many elements of metropolitan, democratic and mass-oriented "culture of attrac-tions", co-creating the peculiar panorama of the ludic modernity of nineteenth-century Warsaw. However, the desire for novelty and the intense, never-satisfy-ing-enough experiences associated with it, characteristic of the popular culture of the time, meant that aeronautical displays were enriched with activities that went beyond the "usual" pattern of take-off, flight and landing. The article includes the descriptions and reconstructions of demonstrations by Joseph G. F. Tradini (1850), who used a live animal tied to a balloon with a large number of ropes in-stead of a gondola. Based on press reports, the Warsaw performances of the leg-endary acrobat and gymnast Leona Dare (1887), who performed gymnastic exer-cises on a trapeze while flying at high altitude, arousing the terror and admiration of the observers, have been reconstructed.